Pendekatan Teknik dan Taktik: Pengaruhnya terhadap Keterampilan Bermain Futsal - Rifqi Festiawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to determine the effect of the Technical approach and tactical approach to the level of futsal playing skills. This research is experimental. The population used is the futsal UKM participants in FIKES Unsoed, totaling 40 people. The sample used in this study was 40 students with a sampling technique that is a total sampling. Data collection techniques in this study used the test. The instrument used in this study was a futsal playing skills test. Data analysis techniques using t-test. The results of this study indicate that there is a significant effect of the practice of a technical approach to futsal playing skills with a Sig (0.002). When seen from the average pretest of 49.05 and the average posttest of 43.01, the Mean Difference figure of 6.04 is obtained, this shows a better chance of 27.25%, the effect of the tactical approach exercise on futsal playing skills stated to have an influence significant with Sig (0,000). When seen from the average pretest of 49.18 and the average posttest of 42.65, a Mean Difference figure of 6.53 was obtained, this indicates that the change is better at 29.36%. Whereas from the results of the independent-t-test it was found that there was no significant difference between the training methods of the Technical and tactic approaches in improving futsal playing skills as indicated by the Sig value (0.890). Conclusion, there is no significant difference between the effect of training using a technical approach and tactics on futsal playing skills Keywords: Tactic and Technical Approaches, Skills, Futsal.